Barrett's esophagus is associated with a distinct oral microbiome. Issue 3 (March 2018) - Snider, Erik J.; Compres, Griselda; Freedberg, Daniel E.; Giddins, Marla J.; Khiabanian, Hossein; Lightdale, Charles J.; Nobel, Yael R.; Toussaint, Nora C.; Uhlemann, Anne‐Catrin; Abrams, Julian A.
Abstract : Objectives: : The esophageal microbiome is composed of predominantly oral flora and is altered in reflux‐related conditions including Barrett's esophagus (BE). Changes to the esophageal microbiome may be reflected in the oral cavity. Assessing the oral microbiome thus represents a potential non‐invasive method to identify patients with BE. Methods: : Patients with and without BE undergoing upper endoscopy were prospectively enrolled. Demographics, clinical data, medications, and dietary intake were assessed. 16S rRNA gene sequencing was performed on saliva samples collected prior to endoscopy. Taxonomic differences between groups were assessed via linear discriminant analysis effect size (LEfSe). Logit models were used to develop microbiome signatures to distinguish BE from non‐BE, assessed by area under the receiver operating curve (AUROC). Results: : A total of 49 patients were enrolled (control = 17, BE = 32). There was no significant difference in alpha diversity comparing all BE patients vs. controls. At the phylum level, the oral microbiome in BE patients had significantly increased relative abundance of Firmicutes ( p = 0.005) and decreased Proteobacteria ( p = 0.02). There were numerous taxonomic differences in the oral microbiome between BE and controls. A model including relative abundance of Lautropia, Streptococcus, and a genus in the order Bacteroidales distinguished BE from controls with an AUROC 0.94 (95% CI: 0.85–1.00). The optimal cutoff identified BE patients with 96.9% sensitivity and 88.2% specificity. Conclusions: : The oral microbiome in BE patients was markedly altered and distinguished BE with relatively high accuracy. The oral microbiome represents a potential screening marker for BE, and validation studies in larger and distinct populations are warranted.